The elasticity of substitution and labour-displacing technical change in post-apartheid South Africa - Friedrich Kreuser; Rulof Burger; Neil Rankin (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper uses normalized constant elasticity of substitution production functions to estimate the elasticity of substitution and labour-augmenting technical change in South Africa over the period 1994-2012. We find elasticities of 0.6-0.9 and positive labour-augmenting technical change, which results in an increase in capital's income share relative to labour. More broadly, we find total factor productivity (TFP) growth rates of between 1 and 2 per cent across industries, although we find no TFP growth in the mining sector. We also find that the sector with the highest TFP growth - agriculture - achieved this through shedding labour while steadily increasing output.
Keywords: E24; O47; O41; 330; elasticity of substitution; labour demand; production functions; technical growth